CMOS RF Circuit Design for Reliability and Variability - Yuan, Jiann-Shiun.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The subject of this book is CMOS RF circuit design for reliability. The device reliability and process variation issues on RF transmitter and receiver circuits will be particular interest to the readers in the field of semiconductor devices and circuits. This proposed book is unique to explore typical reliability issues in the device and technology level and then to examine their impact on RF wireless transceiver circuit performance. Analytical equations, experimental data, device and circuit simulation results will be given for clear explanation. The main benefit the reader derive from this book will be clear understanding on how device reliability issues affects the RF circuit performance subjected to operation aging and process variations.
CMOS Transistor Reliability and Variability -- Wireless Receiver and Transmitter Circuit Reliability -- Low Noise Amplifier Reliability and Variability -- Power Amplifier Reliability and Variability -- Voltage Controlled Oscillator Reliability and Variability -- Mixer Reliability.
Keywords: Electronic circuits; Telecommunication; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications